(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2012)
ABSTRACT This article, based on the Marxist approach and work psychodynamics Christophe Dejours proposes a discussion of the contemporary world of work under the aegis of neoliberalism and the consequences that this brings to the health of the worker, causing suffering not only the employee, but also their family. Keywords: work, neoliberalism, occupational health